Análise da Sensibilidade e Suportabilidade de Medidores Eletrônicos de Energia Elétrica - Rodrigues, Lucas Manuel Resende (2020)
With the advancement of technology, more and more equipment is being manufactured with electronic components among its components, which have the characteristic of being susceptible to short-duration voltage variations (SDVV). Regarding this aspect, in the national and international literature, some studies have shown the behavior of various types of equipment in the face of such phenomena that commonly occur in the electricity distribution network. However, until the present moment, no study has been found aimed at electronic meters, responsible to measure electricity consumption. The main objective of this work is present the behavior of several models of electric energy meters, identifying the nuances of each model in face of the phenomena commented, presenting, for this, sensitivity and supportability curves. In addition, the impacts caused by losing measurement record (due to voltage dips) and the damage to the meter structure (due to voltage rises) are evaluated. It is presented a case study that shows the impact caused by the loss of measurement in a scenario which a certain number of VTCD events were recorded in a real power distribution network.